Different Influence of Pyrimidine and Benzene Rings on Current-Voltage Characteristics of Molecular Devices (Journal of Atomic and Molecular Sciences, 2021)
By using ab initio method and elastic scattering Green’s function theory, the electronic transport properties of symmetric tetraphenyl and non-symmetric diblock dipyrimidinyldiphenyl molecules covalently bonded to two electrodes are investigated. The numerical results show that, the tetraphenyl molecule has better electronic conductivity than thediblock molecule. The latter exhibits pronounced rectification behavior. Those molecularorbitals of the tetraphenyl molecule delocalized into two gold electrodes simultaneouslyresult in better electronic conductivity. However, the non-symmetric structure of the diblock molecule leads to the localization of molecular orbitals, which is a disadvantage toelectronic transport.
Keywords: tetraphenyl molecule; dipyrimidinyldiphenyl molecule; elastic scattering Green’s function; current-voltage characteristic.